APPLICATION OF TOILET TRAINING AND THE HABITS OF ENURESIS IN PRESCHOOL CHILDREN AT KINDERGARTEN DHARMA WANITA PAKEL SUBDISTRICT TULUNGAGUNG REGENCY - Yustanta, Brivian Florentis (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2020)
Toilet training is an attempt by parents to train children to control urination and defecation. Preschool age children consist of children aged 3-6 years and at this age children have begun to be trained in independent toilet training. The impact of parents not applying toilet training makes children have the habit of enuresis. This study aims to determine the correlation between application of toilet training and the habits of enuresis in preschool children at Kindergarten Dharma Wanita Pakel Subdistrict Tulungagung Regency. The study design uses correlation with cross sectional approach. The population was mothers who have preschool children in kindergarten Dharma Wanita as many as 45 mothers with a sample of 40 mothers taken by stratified random sampling technique. The independent variable was the application of toilet training and the dependent variable was the habits of enuresis.Research instrument withÂ questionnaire. The study was conducted on May 9 to 10, 2019 iat Kindergarten Dharma Wanita Pakel Subdistrict Tulungagung Regency. Statistical tests using the chi square test. The results showed that most of the mothers did not apply toilet training in 23 respondents (57.5%) with enuresis children, 22 respondents (55%). Statistical test obtained Ï value 0,000 <Î±: 0.05, then Ho was rejected and H1 was accepted, meaning that there was correlation between application of toilet training and the habits of enuresis in preschool children. Most parents start training when their children are between 2 and 3 years old. Usually physically and emotionally healthy children will be ready at the age of 18 months to 3 years. For boys, it tends to be longer than girls for toilet training. Parents, especially mothers can train children to do toilet training when they have shown that they are ready, so that enuresis habits will disappear. Â Keywords: toilet training, the habits of enuresis, preschool children